Physical exercise therapy for chronic non-specific neck pain: protocol for a meta-analysis of individual participant data - Iresha Dilhari Senarath; Ishanka Weerasekara; Melissa Humphries; Kexun Kenneth Chen; Scott F Farrell; Rutger M J de Zoete (Systematic Reviews)
Abstract Background Every 7 out of 10 people will experience neck pain at some point during their lifetime. A large proportion of these cases will develop into recurrent or chronic conditions. Typically, physical exercise for neck pain seems to be modestly beneficial, but differential effects across participants of randomised trials have not yet been appropriately considered. This individual participant data meta-analysis (IPD MA) will provide a consolidated synthesis of randomised controlled trials (RCTs) that have been conducted to date. We aim to investigate the effectiveness of exercise therapy for chronic non-specific neck pain. Methods/design This study will address the following research questions: (1) what are the effects of exercise therapy compared to no intervention or control interventions on neck pain intensity, pain-related disability, and quality of life? (2) What are the responder and non-responder rates for exercise therapy? (3) What participant characteristics are associated with a clinically meaningful response to exercise therapy? (4) What are the minimal clinically important difference (MCID) and/or minimal detectable change (MDC) values for neck pain intensity, pain-related disability, and quality of life?. This study will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The raw data will be requested from the primary authors of included RCTs. The received original data will be collated into a main datasheet with all the details on every single study, including study details, methodological details, participant demographics, details about intervention and comparison groups, treatment effect modifiers (e.g. workload, medicine usage), and the main outcome measures: pain intensity, pain-related disability, and quality of life. This IPD MA will be performed following a one-step approach, where data from all studies are analysed together while considering the grouping of participants within each study. Risk of bias of included RCTs will be evaluated using the ROB 2.0 tool, and the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) approach will be used to assess the certainty of evidence. Discussion We will analyse IPD of available RCTs exploring the exercise effectiveness for chronic non-specific neck pain. The expected large sample size and consistent presentation of data will allow for further analyses to investigate patient-level heterogeneity in treatment outcomes and the prognosis of chronic non-specific neck pain. Systematic review registration PROSPERO CRD42022323359